RUANG LIMINAL YANG AMBIVALEN: TRADISI DAN MODERNITAS DI LOMBOK DALAM KUMPULAN PUISI LANGIT SEPERTI CANGKANG TELUR BEBEK KARYA IMAM SAFWAN - Muhammad Khairussibyan; Nila Mega Marahayu (Jurnal Lingua Idea, 2018)
This research tried to reveal how the dynamics of contradiction between tradition and modernity in Lombok and how Lombok’s poet Imam Safwan, through a collection of poems of Langit Seperti Cangkang Telur Bebek (LSCTB) addressed the issue of tradition and modernity. The purpose of this study is to reveal the forms of conflict between modernity and tradition in Lombok dan view the poet’s attitude toward the conflict. The theory and analysis method of the binary opposition of Yuri Lotman’s semiotic were used to dismantle the structure and ideology of Imam Safwan’s poems. This study found that the problems of tradition and modernity in Lombok was found in the poems of Imam Safwan. Coping with this problem, Imam Safwan’s poems show ambivalence that the evaluation of two semiosphere (tradition and modernity) was conducted in turn. In a poem, Imam evaluated tradition from the point of view of modernity but in other poetry, Imam evaluated modernity from the point of view of tradition. This ambivalent attitude shows that Imam occupies the border of the semiosphere or the liminal space ini which tradition and modernity seek to be negotiated.